Case studies in crowd management, security and business continuity / edited by Chris Kemp and Patrick Smith. - Kemp, Chris; Smith, Patrick (Great Shelford : Entertainment Technology Press, 2010)
This book focuses on a series of events that had major crowd management issues impacting on the every day delivery of the events researched.
Keywords: Crowd control; Special events